Inferno [videorecording (DVD)] - Hanks, Tom; Jones, Felicity; Khan, Irrfan, 1967-2020-; Brown, Dan, 1964- (Sony Pictures Home Entertainment, 2017)
When Robert Langdon wakes up in an Italian hospital with amnesia, he teams up with Sienna Brooks, a doctor he hopes will help him recover his memories. Together, they race across Europe and against the clock to stop a madman from unleashing a global virus that would wipe out half of the world's population.